Biofouling on buoyant marine plastics: An experimental study into the effect of size on surface longevity. (March 2016) - Fazey, Francesca M.C.; Ryan, Peter G.
Abstract: Recent estimates suggest that roughly 100 times more plastic litter enters the sea than is found floating at the sea surface, despite the buoyancy and durability of many plastic polymers. Biofouling by marine biota is one possible mechanism responsible for this discrepancy. Microplastics (<5 mm in diameter) are more scarce than larger size classes, which makes sense because fouling is a function of surface area whereas buoyancy is a function of volume; the smaller an object, the greater its relative surface area. We tested whether plastic items with high surface area to volume ratios sank more rapidly by submerging 15 different sizes of polyethylene samples in False Bay, South Africa, for 12 weeks to determine the time required for samples to sink. All samples became sufficiently fouled to sink within the study period, but small samples lost buoyancy much faster than larger ones. There was a direct relationship between sample volume (buoyancy) and the time to attain a 50% probability of sinking, which ranged from 17 to 66 days of exposure. Our results provide the first estimates of the longevity of different sizes of plastic debris at the ocean surface. Further research is required to determine how fouling rates differ on free floating debris in different regions and in different types of marine environments. Such estimates could be used to improve model predictions of the distribution and abundance of floating plastic debris globally. Highlights: We tested how fragment size affects the rate of buoyancy loss at sea due to biofouling for two low-density plastic polymers. We found a strong direct relationship between fragment size and surface longevity. Our longevity estimates ranged from 17 days for the thinnest microplastics to 66 days for thicker macroplastics. Our results provide the first estimates of the longevity of different sizes of plastic debris at the ocean surface. The results could be used to improve model predictions of the dispersal of floating plastic debris. Abstract : This paper demonstrates the effect of biofouling on the buoyancy and surface longevity of marine plastic debris of different sizes and thicknesses.